PENILAIAN KAPASITAS PENERIMA PINJAMAN USAHA MIKRO DARI PSE KEUSKUPAN SURABAYA - Lilik Indrawati (Politeknik Ubaya, 2017)
In Indonesian economic development, micro, small and medium enterprise aredescribed as sectors having important roles since the majority of Indnesianpopulation belong to the low-educated group and live on small schale enterpriseboth in traditional and modern ones. Micro, small and medium enterprise existas one of the solutions to the sound economic system. These enterprises are theones which are not affected by the economic crisis and the global economiccrisis. Looking at this facts, these two enterprises should be taken into account bythe government in the economic development. The micro, small and mediumenterprise get the capital from the bank, both government and private bank. Sois the one organized by Surabaya Diosis via the Comission of social and economicdevelopment for the members and public. This article is aimed at evaluatingthe the capacity of the micro loan reveiver from the Comission of social andeconomic development.